Penyuluhan kesehatan gigi dan mulut menggunakan media poster pada siswa Sekolah Dasar - Utari Zulkaidah; Rezki Dirman; Sultan Amin Yasin; Supiana Supiana (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Oral health is a crucial component of general health that supports a child's growth and development. However, oral diseases particularly dental caries remain prevalent health issues among school-aged children. Purpose: To enhance students' knowledge regarding oral hygiene and the prevention of oral diseases through the use of posters. Method: The community service activity was carried out on Saturday, April 18, 2026, at Elementary School 34 Paconne, North Belopa District, Luwu Regency, South Sulawesi. The initiative aimed to impart knowledge and teach oral hygiene practices to children, involving 40 students from SD 34 Paconne as participants. Knowledge levels were assessed using questionnaires administered before (pre-test) and after (post-test) the educational session. Evaluation was carried out through direct observation and descriptive analysis, comparing pre-test and post-test scores regarding oral health. Results: A shift in students' knowledge levels was observed following the poster-based educational activity; students participated enthusiastically, engaged actively in the Q&A session, and successfully demonstrated correct tooth-brushing techniques. There was a marked improvement in the students' oral health knowledge: the proportion of students with a